Stigma in help-seeking: the case of adolescents. Issue 1 (2nd January 2018) - Shechtman, Zipora; Vogel, David L.; Strass, Haley A.; Heath, Patrick J.
ABSTRACT: Stigma associated with seeking help has been found to be a key help-seeking barrier, however its role is less clear for: (a) adolescents, (b) groups outside the United States and (c) different types of therapy. This study addresses these omissions by examining the relationships between perceptions of public stigma of mental illness and the self-stigma of seeking help, and how they are related to help-seeking attitudes and intentions for both individual and group therapy among adolescents in Israel ( N  = 238). Path analysis confirmed that self-stigma of seeking help was negatively related to attitudes towards psychological help which was then positively related to intentions to seek help, across both individual and group therapy. Consistent with the only other study conducted in Israel, but contrasting research from other parts of the world, the relationship between perceptions of public stigma of mental illness and self-stigma of seeking help was not present for either individual or group therapy. However, perceptions of public stigma of mental illness were a direct negative predictor of help-seeking attitudes for group therapy. Overall, participants reported more negative perceptions of group therapy than individual therapy. These results have implications for future interventions to increase help-seeking behaviours for adolescents.